Kepastian Hukum dalam Penerapan Sistem Perizinan dan Penangkapan Ikan di Indonesia: Pendekatan Normatif - Emil Salim Siregar; Syarizal Azis Harahap; M. Bryantara Ramadhan; Dwi Silviani; Bima Aslam Anugerah (J-CEKI : Jurnal Cendekia Ilmiah, 2026)
This study examines the effectiveness of Indonesia’s fishing licensing system by focusing on legal certainty, regulatory consistency, and the implementation of norms in practice. Although the fisheries legal framework is regulated through various laws and regulations, its implementation still faces several challenges, including regulatory overlap, weak supervision, and widespread illegal, unreported, and unregulated (IUU) fishing practices. Using a normative legal approach, this research analyzes the alignment between existing legal norms and their practical application. The findings indicate that legal uncertainty and inconsistent regulatory enforcement are the main factors hindering the effectiveness of the licensing system. Therefore, strengthening regulations, harmonizing legal provisions, and optimizing supervisory functions are necessary to ensure that the fisheries licensing system can support orderly, fair, and sustainable fisheries governance.